2001
DOI: 10.1002/1097-0142(20010415)91:8<1458::aid-cncr1153>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of intracranial and spinal tumors in patients with Down syndrome and report of a rapidly progressing Grade 2 astrocytoma

Abstract: Cerebral tumors in patients with DS have a specific distribution and may behave differently compared with the general population. These features may be related to the gene dosage effect of oncogenes, antioncogenes, and genes involved in cerebral development due to the supernumerary chromosome 21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
(26 reference statements)
1
8
0
Order By: Relevance
“…Most studies have suggested a decreased incidence of intracranial tumors 9,20–23 . Thirty‐eight reported cases with intracranial and spinal tumors were summarized by Satgé et al 24 . In our study, two (1 month of age and 6 years of age) out of three cases with central nervous system tumors were identified as germ cell tumors (Table 5).…”
Section: Discussionsupporting
confidence: 53%
“…Most studies have suggested a decreased incidence of intracranial tumors 9,20–23 . Thirty‐eight reported cases with intracranial and spinal tumors were summarized by Satgé et al 24 . In our study, two (1 month of age and 6 years of age) out of three cases with central nervous system tumors were identified as germ cell tumors (Table 5).…”
Section: Discussionsupporting
confidence: 53%
“…However, Asian patients with DS do not have a lower risk of brain tumors, especially germ cell tumors [2]. Satge et al summarized 38 central nervous system tumors in DS and reported that 14 (61%) of 23 cases under age 15 were germ cell tumors [3]. All reported cases were Asian, and yolk sac tumors (YST) had the highest occurrence.…”
Section: Introductionmentioning
confidence: 66%
“…BDNF is a neurotrophin that plays a key role in neurogenesis and the maintenance of neuronal plasticity by binding specifically to tropomyosin-related kinase receptor B [11]. Brain tumors in patients with DS exhibit a specific distribution, and differ from those of the general population [12]. On autopsy, DS has been found to be associated with neuroanatomical abnormalities in the corpus callosum, ventricular hypertrophy, and malformations of the cerebellum, frontal lobe, temporal lobes, and brain stem [13,14].…”
Section: Discussionmentioning
confidence: 99%